Estudios sobre la Universidad de Lérida (1561-1717) - Ramis Barceló, Rafael (Historia de las Universidades, 2018)
This book, written by Rafael Ramis-Barceló, brings together three studies on the University of Lleida (1561-1717). The first is a description of the Studium of Lleida during the pontificate of Antonio Agustín. It was a Golden Age, with great professors, although with frequent conflicts. The second is an analysis of the Faculty of Civil and Canon Law from the death of Felipe V until the transfer of the University to Cervera. The third deals with the Faculties of Arts and Theology for the same period. These two final chapters study the decline of the University and its problems during the Baroque Age. The book -with new sources, from different Catalan archives- aims to offer an overview of the last period of the Studium of Lleida and its intricate transfer to Cervera.----------Este libro, escrito por Rafael Ramis-Barceló, reúne tres estudios sobre la Universidad de Lérida (1561-1717). El primero es una descripción del Estudio de Lérida durante el pontificado de Antonio Agustín. Fue una época dorada, con grandes maestros, aunque con frecuentes conflictos. El segundo es un análisis de la Facultad de Leyes y Cánones desde el fallecimiento de Felipe V hasta la transferencia de la Universidad a Cervera. El tercero trata las Facultades de Artes y de Teología durante el mismo período. Estos dos capítulos finales inciden en la decadencia de la Universidad y a los problemas que tuvo que afrontar durante el Barroco. El libro -con fuentes novedosas, procedentes de diferentes archivos catalanes- pretende ofrecer una panorámica de la última etapa del Estudio de Lérida y de su compleja transferencia a Cervera.